Confirming Information Flows in Networks - Pascal Billand; Christophe Bravard; Jurjen Kamphorst; Sudipta Sarangi (Tinbergen Institute, 2012)
Social networks, be it on the internet or in real life, facilitate information flows. We model this by giving agents incentives to link with others and receive information through those links. In many networks agents will value confirmation of the information they receive from others. Our paper analyzes the impact such a need for confirmation has on the social networks which are formed. We first study the existence of Nash equilibria and then characterize the set of strict Nash networks. Next, we characterize the set of strictly efficient networks and discuss the relationship between strictly efficient networks and strict Nash networks.
urn:NBN:nl:ui:15-1765/31779
Keywords: C72; D85; 330; connections model; confirmation; two-way flow models; Soziales Netzwerk; Informationsverbreitung; Nash-Gleichgewicht; Nichtkooperatives Spiel; Theorie